2020
DOI: 10.3390/polym12061391
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static Tests of Hybrid Adhesive Bonds Based on Biological Reinforcement in the Form of Eggshell Microparticles

Abstract: The paper is focused on the research of the cyclic loading of hybrid adhesive bonds based on eggshell microparticles in polymer composite. The aim of the research was to characterize the behavior of hybrid adhesive bonds with composite adhesive layer in quasi-static tests. An epoxy resin was used as the matrix and microparticles of eggshells were used as the filler. The adhesive bonds were exposed to cyclic loading and their service life and mechanical properties were evaluated. Testing was performed by 1000 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…The evaluation of measured data was performed by means of the program STATISTICA, by an ANOVA F-test, i.e., the hypothesis H 0 presents a statistically insignificant difference among the measured data ( p > 0.05), and the hypothesis H 1 presents a refusal of the hypothesis H 0 , i.e., there is a statistically significant difference among the measured data ( p < 0.05) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of measured data was performed by means of the program STATISTICA, by an ANOVA F-test, i.e., the hypothesis H 0 presents a statistically insignificant difference among the measured data ( p > 0.05), and the hypothesis H 1 presents a refusal of the hypothesis H 0 , i.e., there is a statistically significant difference among the measured data ( p < 0.05) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…The strength and service life of adhesive bonds are decreased even by low stress values with cyclic degradation. Cyclic (quasi-static) tests are necessary for practical application of adhesive bonds [ 30 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…The surface of the adherends was mechanically treated in a blasting cabin using abrasive Garnet MESH 80 and then chemically treated in an acetone bath just before bonding. These methods for surface treatments were proven as optimal in terms of mechanical properties of adhesive bonds by several studies [45,48]. The roughness of adherends' surfaces were measured using profilometer Mitutoyo Surftest 301 (Mitutoyo Europe GmbH, Neuss, Germany).…”
Section: Bonded Materials (Adherend)mentioning
confidence: 99%
“…The tests of cyclic loading are essential for practical application of adhesive bonds [42][43][44]. The researchers demonstrated that the hybrid composite layer of adhesive bonding can positively influence the mechanical properties and extend their service life under cyclic loading [19,35,45].…”
Section: Introductionmentioning
confidence: 99%